Complete mitochondrial genome of the hawkmoth Notonagemia analis scribae (Lepidoptera: Sphingidae) - Kim, Min Jee (Mitochondrial DNA B Resour, 2016)
Currently, the mitochondrial genome of only two species of Sphingidae have been completely sequenced. For the phylogenetic study of Bombycoidea (including Bombycidae, Saturniidae and Sphingidae) using mitochondrial genomes (mitogenomes), more species are required as a basis for future research. In the present study, we sequenced the complete mitogenome of the hawkmoth, Notonagemia analis scribae (Lepidoptera: Sphingidae), to enrich the Sphingidae database. The length of the N. a. scribae genome was 15,303 bp with a typical set of genes (13 protein-coding genes [PCGs], 2 rRNA genes, and 22 tRNA genes), and one major non-coding A + T-rich region. The COI gene had a CGA start codon, which is the start codon for this gene in the majority of lepidopteran species, whereas other PCGs began with ATN codons. A 318-bp A + T-rich region harbored the blocks of conserved sequences that are typically found in lepidopteran insects, excluding a poly-A stretch, which is typically found at the end of the A + T-rich region. Phylogenetic analysis using the 13 PCGs indicated that N. a. scribae grouped together with two within-familial species, Sphinx morio and Manduca sexta, with the highest nodal support both by Bayesian inference and maximum-likelihood methods, forming the Sphingidae monophyletic group.